2021
DOI: 10.1149/1945-7111/ac2c13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Solvent-Dependent Ink Structure and Catalyst Layer Morphology Based on Ink Sedimentation Dynamics and Catalyst-Ionomer Cast Films

Abstract: Ink structure is of great research interest because it influences the catalyst layer microstructure and ultimately determines fuel cell performance. To improve understanding of the ink structure, particle size distribution and ink sedimentation dynamics were characterized in this study by performing acoustic spectroscopy (AS) and analytical centrifugation (AC) analyses, respectively, using actual concentrations of Pt/C inks (10.4 wt% of solid content) without dilution. For the catalyst inks prepared with 1-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…During the ink preparation process, the components of the ink interact with each other to form a structure. The interaction between the catalyst and solvent determines the size of the catalyst aggregation, the interaction between the ionomer and solvent determines the size and shape of the ionomer, and the interaction between the catalyst and ionomer affects the adsorption form of the ionomer on the catalyst surface, thus altering the ink structure [13,21]. Ultimately, the final structure of the ink is determined as a result of interactions that minimize the free energy of the ink system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the ink preparation process, the components of the ink interact with each other to form a structure. The interaction between the catalyst and solvent determines the size of the catalyst aggregation, the interaction between the ionomer and solvent determines the size and shape of the ionomer, and the interaction between the catalyst and ionomer affects the adsorption form of the ionomer on the catalyst surface, thus altering the ink structure [13,21]. Ultimately, the final structure of the ink is determined as a result of interactions that minimize the free energy of the ink system.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the role of polymers as stabilizers in colloid systems has been reported for a long time [27], and research is ongoing to elucidate the interactions between particles, polymers, and solvents in colloid systems [28]. In ink systems for fuel cells, the degree of aggregation of ionomers and adsorption of catalysts vary depending on the solvent [21], but their influence on ink stability appears to be relatively minor. In ink systems including ionomers, there are limitations in examining differences in ink structure depending on the solvent only through ink sedimentation analysis, and therefore, the rheological characteristics of the ink were examined.…”
Section: Ink Sedimentation Behaviormentioning
confidence: 99%
“…35,36 For the successfully commercialized perfluoro sulfonic acid (PFSA) ionomers used in PEMFCs, 37 the dielectric constant (ε) and solubility parameter (δ) of the organic dispersion solvent were identified as the key parameters affecting the conformation and surface charge of the PFSAtype Nafion ionomer in the solution. 33,34,38,39 A previous study suggested that the pK a of the solvent can affect the porous structure of membranes cast from phosphonic acid ionomer dispersion through the acid−base interaction between ionomer and solvent. 40 By tuning the solvent, the interactions between the ionomer and catalyst can be optimized, leading to the formation of a three-dimensional (3D) network in ink and, ultimately, a well-connected carbon-ionomer network in the CLs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The microstructure of CL is affected by the composition of the catalyst ink and the preparation techniques (such as spray-coating, transfer printing, or screen printing) for both AEMFCs and proton exchange membrane fuel cells (PEMFCs). When a specific preparation technique is used, the microstructure of the CL is controlled by the interactions between the ionomer and catalyst in ink during the dispersing and drying processes under the strong influence of solvent environment. In addition, the surface functional groups affect the surface charge of carbon support in dispersion solvent, which in turn significantly affects the dispersibility of ink. , For the successfully commercialized perfluoro sulfonic acid (PFSA) ionomers used in PEMFCs, the dielectric constant (ε) and solubility parameter (δ) of the organic dispersion solvent were identified as the key parameters affecting the conformation and surface charge of the PFSA-type Nafion ionomer in the solution. ,,, A previous study suggested that the p K a of the solvent can affect the porous structure of membranes cast from phosphonic acid ionomer dispersion through the acid–base interaction between ionomer and solvent . By tuning the solvent, the interactions between the ionomer and catalyst can be optimized, leading to the formation of a three-dimensional (3D) network in ink and, ultimately, a well-connected carbon-ionomer network in the CLs. ,,, The well-connected network structure helps maintain the continuity of the Nafion ionomer and the high porosity of the CL, resulting in high mass-transport rate and proton conductivity. ,, …”
Section: Introductionmentioning
confidence: 99%